Presence of diphenyl phosphate and aryl-phosphate flame retardants in indoor dust from different microenvironments in Spain and the Netherlands and estimation of human exposure. (March 2018) - Björnsdotter, Maria K.; Romera-García, Encarnación; Borrull, Josep; de Boer, Jacob; Rubio, Soledad; Ballesteros-Gómez, Ana
Abstract: Phosphate flame retardants (PFRs) are ubiquitous chemicals in the indoor environment. Diphenyl phosphate (DPHP) is a major metabolite and a common biomarker of aryl-PFRs. Since it is used as a chemical additive and it is a common impurity of aryl-PFRs as well as a degradation product, its presence in indoor dust as an additional source of exposure should not be easily ruled out. In this study, DPHP (and TPHP) are measured in indoor dust in samples collected in Spain and in the Netherlands ( n  = 80). Additionally, the presence of other emerging aryl-PFRs was monitored by target screening. TPHP and DPHP were present in all samples in the ranges 169–142, 459 ng/g and 106–79, 661 ng/g, respectively. DPHP concentrations were strongly correlated to the TPHP levels (r = 0.90, p < 0.01), suggesting that DPHP could be present as degradation product of TPHP or other aryl-PFRs. Estimated exposures for adults and toddlers in Spain to TPHP and DPHP via dust ingestion (country for which the number of samples was higher) were much lower than the estimated reference dose (US EPA) for TPHP. However, other routes of exposure may contribute to the overall internal exposure (diet, dermal contact with dust/consumer products and inhalation of indoor air). The estimated urinary DPHP levels for adults and toddlers in Spain (0.002–0.032 ng/mL) as a result of dust ingestion were low in comparison with the reported levels, indicating a low contribution of this source of contamination to the overall DPHP exposure. Other aryl-PFRs, namely cresyl diphenyl phosphate (CDP), resorcinol bis(diphenyl phosphate) (RDP), 2-ethylhexyl diphenyl phosphate (EDPHP), isodecyl diphenyl phosphate (IDP) and bisphenol A bis(diphenyl phosphate) (BDP), were all detected in indoor dust, however, with lower frequency. Graphical abstract: Highlights: TPHP and DPHP were present at high concentrations in all samples analyzed. A strong correlation between DPHP and TPHP concentrations in dust was observed. Estimated exposures to TPHP via dust ingestion are lower than the reference dose. DPHP levels in dust are insufficient to explain urinary levels via dust ingestion.